A full-plane block Kalman filter for image restoration - Citrin, Stuart, author; Azimi-Sadjadi, Mahmood R., author; IEEE, publisher (Colorado State University. Libraries, 1992)
A new two-dimensional (2-D) block Kalman filtering method is presented which uses a full-plane image model to generate a more accurate filtered estimate of an image that has been corrupted by additive noise and full-plane blur. Causality is maintained within the filtering process by employing multiple concurrent block estimators. In addition, true state dynamics are preserved, resulting in an accurate Kalman gain matrix. Simulation results on a test image corrupted by additive white Gaussian noise are presented for various image models and compared to those of the previous block Kalman filtering methods.
Keywords: two-dimensional digital filters; image reconstruction; Kalman filters; filtering and prediction theory